Criminal Law Enforcement against Illegal Gold Mining (Study of Decision No. 153/Pid.Sus/2023/PN.Mdl): Penegakan Hukum Pidana terhadap Pertambangan Emas Ilegal (Studi Putusan No. 153/Pid.Sus/2023/PN.Mdl) - Melati, Xhifa Mayputeri; Panjaitan, Budi Sastra (Rechtsidee, 2025)
General Background: Illegal gold mining has long served as a vital economic lifeline for communities in Lingga Bayu District, Mandailing Natal Regency. Specific Background: Despite its deep-rooted presence and socio-economic significance, such mining activities persist without formal governmental authorization, creating tension between legal norms and community livelihoods. Knowledge Gap: Existing legal enforcement often emphasizes punitive action, yet overlooks the structural socio-economic challenges faced by traditional miners. Aims: This study examines the implementation of criminal law enforcement against illegal gold mining and evaluates the fairness and justice outcomes of Decision Number 153/Pid.Sus/2023/PN Mdl by the Mandailing Natal District Court. Results: Findings indicate that while law enforcement adheres to normative legal standards and ensures legal certainty, it falls short in delivering substantive justice and long-term legal benefits for local miners. Novelty: The study highlights the misalignment between repressive legal mechanisms and the socio-cultural realities of community-based mining practices, advocating for a shift from a purely legalistic approach to one that is humanistic and transformative. Implications: The research suggests a need for integrative legal reform, including affirmative policies for people's mining legalization, to achieve holistic and sustainable justice for marginalized mining communities. Highlights: Highlights the gap between legal enforcement and local socio-economic realities. Critiques the repressive nature of criminal law against traditional miners. Proposes a transformative and inclusive legal reform model. Keywords: Illegal Mining, Law Enforcement, Community Justice, Court Decision, Humanistic Approach